Polymers in organic electronics : polymer selection for electronic, mechatronic & optoelectronic systems - Khalifeh, Sulaiman, 1959- (ChemTec Publishing, 2020)
"Electronics (including micro, nano, and quantum systems); mechanics (including MEMS, NEMS, MOEMS, and NOEMS); mechatronics (including robots, artificial muscles, and automated air vehicles); informatics (including software, hardware, and communication); materials science (including conjugated polymers, smart materials, and conducting small molecules); and optoelectronics (optical fibers and lenses) are the critical elements of development in science today. An integration is the practical concept by which these elements are combined and implemented; so that a new high performance, low cost, and lightweight organic electronic components (devices or systems) can be produced with shorter lead time. Organic electronics or polymer electronics represent the important branch of material science dealing with electrically conductive polymers and small conductive molecules of carbon-based nature. This branch focuses on optimizing the semi-conductivity, conductivity, light emitting properties of organic materials (polymers, oligomers, and small molecules), and hybrid composites having organic-inorganic structures."--